800 words. Season 2, part 2 [videorecording (DVD)] - Thompson, Erik, 1959-; Vidler, Melinda; Anthony, Benson Jack, 1997- (RLJ Entertainment, 2017)
After the death of his wife, newspaper columnist George Turner decided to move his family from Sydney to the small New Zealand seaside town of Weld. He wanted his kids, Shay and Arlo, to have a fresh start, but all did not go according to plan. In Season Two George must reunite his family and bring Shay home from her self-appointed exile in Australia. George is also finding out what it means to be a local in the quirky town of Weld.